The use of politeness strategies in the classroom context by English university students - Mahmud, Murni (Universitas Pendidikan Indonesia, 2019)
Politeness still becomes a major concern in English language teaching. It is considered as one way to maintain effective classroom interaction. Therefore, as one of the important actors in the class, teachers, and students need to practice politeness as a way to create effective classroom interaction. This study aims to explore the politeness strategies of English students at one of the universities in Makassar. The researcher applied a descriptive qualitative research method to explore the politeness phenomena in EFL classroom interaction. The participants of this research were two classes of English literature program consisting of 50 students. The primary sources of data were the individual student presentations which had been recorded. There were fifty transcriptions of the recording which lasted for five to seven minutes for each presentation. The transcriptions were analyzed and discussed based on the theory of politeness of Brown and Levinson (1987). The findings from this study revealed that English students used different kinds of expressions to encode their politeness in the class. Those expressions were in the forms of greetings, thanking, addressing terms, apologizing, and fillers. There were also some terms derived from students’ vernacular language which were used as a softening mechanism for their presentation. These expressions were categorized as positive and negative politeness. The findings of this study might be used as an input for teachers and students in an effort to create effective classroom interaction.